2014
DOI: 10.3923/pjbs.2014.891.897
|View full text |Cite
|
Sign up to set email alerts
|

Detection P53 Gene Deletion in Hematological Malignancies Using Fluorescence In situ Hybridization: A Pilot Study

Abstract: P53 as a tumor suppressor gene plays a major role in cancer development, it is essential for cell growth regulation and apoptosis. The deletion of p53 is known to be associated with aggressive diseases in several hematological malignancies. The evidence indicated that p53 deletions can be acquired as a result of chemotherapy. Therefore, a follow-up study for p53 gene deletion by fluorescence in situ hybridization technique (FISH) was carried out for the patients group who affected with different hematological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…TP53 deletion was identi ed in about 62.5% of all investigated child samples, whereas the deletion was detected at a lower rate (16%) of adult cases. Furthermore, the highest average of TP53 deletion has been noticed in patients with ALL (55%), which is in concordance with and even higher than what was reported by other studies (56%) 45 .…”
Section: Discussionsupporting
confidence: 91%
“…TP53 deletion was identi ed in about 62.5% of all investigated child samples, whereas the deletion was detected at a lower rate (16%) of adult cases. Furthermore, the highest average of TP53 deletion has been noticed in patients with ALL (55%), which is in concordance with and even higher than what was reported by other studies (56%) 45 .…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that, TP53 deletion was identified in about 62.5% of all investigated child samples, whereas the deletion was detected at a lower rate (16%) of adult cases. Furthermore, the highest average of TP53 deletion has been noticed in patients with ALL (55%), which is in concordance with and even higher than what was reported by other studies (56%) [46]. TP53 changes were mainly seen in a hypodiploid subtype of ALL, mainly due to germline changes, which changed the disease manifestation to Li-Fraumeni syndrome.…”
Section: Discussionsupporting
confidence: 88%